Maqashid Syariah Dalam Khiyar dan Implementasinya Pada Jual Beli : (Studi Kasus Praktek Khiyar Di Pasar Ikan lama Medan) - Yati, Hida (Jurnal Ekonomi dan Keuangan Syariah, 2022)
Basically, Islam is a perfect religion covering all areas of human life. Assets in the Islamic economic system have an important position. In relation to economic business activities and rituals of worship, property is properly considered so that in maqashid sharia it becomes one of the important points, namely maintaining or safeguarding property. This study aims to determine the implementation of khiyar in buying and selling transactions at the Medan Lama Fish Market. The approach used in this study is a qualitative approach with data collection techniques through interviews, documentation and observation. The results of this study have implemented khiyar by Muslim shop owners in the old field fish market, which has implemented three types of khiyar, namely khiyar assembly, khiyar disgrace and khiyar prerequisite.